Pengembangan Mobile Application: Flores Library - Gaol, Tiurma Lumban; Pasaribu, Monalisa; Panjaitan, Goklas; Sianipar, Evan Richardo; Naomi, Poibe Leny; Desrony, Vicktor Lambok (TEMATIK, 2022)
The presence of a library is very much needed as an effort to form superior human resources. The Flores library was established in Pea Nature Village to provide reading materials that can increase the knowledge of the audience in Pa Nature Village. However, the library in question still does not have an information system that can assist users in conducting information retrieval. On the other hand, currently, information technology is developing very fast. The library information system application is expected to help fulfill the need for access to information and information retrieval. Mobile application is the selected application in the development of library information systems. The use of mobile applications will make it easier for users to access information on a mobile basis. This application can also assist in tracing the collection and also the status of the collection of library materials in the Flores Library.